The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5530/pc.2017.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Swainsona Formosa (G.Don) Joy Thomp. Solvent Extractions Inhibit the Growth of a Panel of Pathogenic Bacteria

Abstract: Introduction: Swainsona formosa is a legumous plant which is endemic to the arid inland regions of Australia. Several Swainsona spp. were valued by the first Australian for their antiseptic properties and were used traditionally to treat a variety of bacterial diseases. Despite this, S. formosa solvent extractions have not been rigorously examined for antibacterial properties against many bacterial pathogens. Methods: The antimicrobial activity of S. formosa leaf extracts was investigated by disc diffusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[1,2] A recent study has also reported bacterial growth inhibitory activity for S. formosa leaf extracts against wide range of gram positive and gram negative bacteria. [3] A defining phytochemical characteristic of many Swainsona spp. is the presence of the indolizidine alkaloid phytotoxin swainsonine.…”
Section: Medicinal Plant Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] A recent study has also reported bacterial growth inhibitory activity for S. formosa leaf extracts against wide range of gram positive and gram negative bacteria. [3] A defining phytochemical characteristic of many Swainsona spp. is the presence of the indolizidine alkaloid phytotoxin swainsonine.…”
Section: Medicinal Plant Imagesmentioning
confidence: 99%
“…were considered particularly useful as antiseptics and as bacteriocide chemotherapies against a broad spectrum of bacterial pathogens [1,2]. A recent study has also reported bacterial growth inhibitory activity for S. formosa leaf extracts against wide range of gram positive and gram negative bacteria [3]. A defining phytochemical characteristic of many Swainsona spp.…”
mentioning
confidence: 99%
“…[3][4] A recent study has also reported bacterial growth inhibitory activity for S. formosa leaf extracts against wide range of gram positive and gram negative bacteria. 5 A defining phytochemical characteristic of many Swainsona spp. is the presence of the indolizidine alkaloid phytotoxin swainsonine.…”
Section: Medicinal Plant Imagesmentioning
confidence: 99%